Late Mughal Period Tombs in Khyber Pakhtunkhwa, Pakistan - Shakirullah (Ancient Pakistan, 2021)
After the death of Aurangzeb Alamgir, the Mughal Empire showed a clear sign of disintegration and the feeble descendents of the Great Mughal did not retain the same position. Due to unfavourable environment building activities also slowed down so that only a few buildings of this period may be seen in Khyber Pakhtunkhwa. One of them is the tomb of Sayyid Abd al-Wahab alias Akhund Panju Baba at Akbarpura near Peshawar and the second is the burial place of Doda Baba in Bajaur Agency in the main graveyard of Doda village in the Nawagai area. Both the tombs are the sole example of the late Mughal period in this locality and no detail study are carried out before. In the present study comprehensive documentations of both the monuments are done with analytical study.